Experimental analysis on parameters affecting drag force on speed skaters - Oggiano, L.; Saetran, L. R. (Sports Technology, 2010)
In sports where high speed is reached and drag is the main force acting on the athlete's body, the posture highly influences the total drag. In speed skating, due to the fact that the total drag is proportional to the frontal area, the athletes minimize their frontal area keeping the trunk parallel to the air flow. In this study it is shown that the aerodynamic resistance acting on the legs counts up to 1/3 of the total drag. In order to reduce the drag, rough textiles with different patterns have been used in sport suits. However, a certain number of parameters need to be considered in order to optimize the aerodynamic performance of a textile. These parameters are: speed, diameter of the leg, yaw angle, distance between the legs and roughness of the textile. This study shows a quantitative effect of the different parameters on the aerodynamic performances of textiles. Tests have been carried out on cylinder models and c D -speed curves for each case have been acquired. The contemporary effect of roughness and the diameter, roughness and yaw angle and roughness and distance between the legs have been highlighted with the main conclusion that rough textiles are not always beneficial in terms of drag reduction. However, an accurate choice of the different materials for different speed, yaw angles, size of the model and distance between the legs could improve the overall aerodynamic properties reducing the drag.